P2X3 receptor expression in dorsal horn of spinal cord and pain threshold after estrogen therapy for prevention therapy in neuropathic pain. (December 2020) - Rosyidi, Rohadi Muhammad; Priyanto, Bambang; Wardhana, Dewa Putu Wisnu; Prihastomo, Krisna Tsaniadi; Hikmi, Syauq; Turchan, Agus; Rozikin,
Abstract: Introduction: Neuropathic pain may arise from conditions that affecting the central or peripheral nervous system. This study was held to determine the difference P2X3 receptor expression in the dorsal horn of the spinal cord and pain threshold after estrogen therapy in neuropathic pain. Methods: This study design was an experimental research laboratory. The 24 mice samples divided into negative control group, positive control, and treatment groups. The treatment groups were given subcutaneous injections of estrogen 0.4 ml and also examined for the onset of thermal hyperalgesia in every rat. On day 15, an autopsy was performed on rats, and the spine was taken. The spinal cord was stained by hematoxylin-eosin, and the expression of P2X3 receptors was investigated. P2X3 receptor expression was examined in the dorsal horn on each sample. Results: From 24 subjects of the study revealed an increase in the onset of thermal hyperalgesia on the estrogen group compared with the placebo group, a higher start. This study also obtained a decrease in the expression of P2X3 on the therapy group compared to the positive control group with significant differences. Statistical test results revealed the appearance of the P2X3 estrogen group had a substantial difference with the placebo group (p = 0.000) and the mean of the negative control group (p = 0.030). The placebo group had a significant difference from the negative control group (p = 0.035). Conclusion: Estrogen could decrease the expression of P2X3 receptors and prolonged the onset of thermal hyperalgesia. So, both of these explained that estrogen has a role in preventing the occurrence of neuropathic pain after peripheral nerve lesions. Highlights: Experimental study on mice subjects to determine the difference P2X3 receptor expression in the dorsal horn of spinal cord. Pain threshold after estrogen therapy in neuropathic pain. Estrogen could decrease the expression of P2X3 receptors. Estrogen prolonged the onset of thermal hyperalgesia.